How Does Unconventional Monetary Policy Influence the Economy in Japan? - Otsubo, Kansho Piotr (Asian Economic and Financial Review, 2018)
This paper investigates the transmission mechanism of unconventional monetary policies by estimating a time-varying parameter structural vector auto-regression (TVP-VAR) model using Japanese monthly data beginning with the implementation of quantitative easing in 2001. The results of the empirical study can be summarized in four points. First, the accumulated impulse responses of stock prices and exchange rates to a positive monetary policy shock are significant increases and significant depreciation, respectively, in the early days of all unconventional monetary policy periods. Second, a monetary policy shock does not increase bank lending for all unconventional monetary policies. Third, the relationship between an increase in stock prices and the depreciation of exchange rates and increase in GDP has changed since the beginning of Abenomics. Fourth, the accumulated impulse responses of the inflation rate to a positive monetary policy shock became a significant increase during and after the comprehensive monetary easing in October 2010 due to the clarification of the policy duration, and the responses become remarkable after inflation targeting was introduced in January 2013. The first and second results imply that the main transmission channel of unconventional monetary policy in Japan is stock prices and the exchange rate.